Analysis of security CMS platforms by vulnerability scanners - Zamościński, Patryk; Kozieł, Grzegorz (Journal of Computer Sciences Institute, 2020)
Subject of security the most popular CMS platforms has been undertaken in the following thesis. There were introduced fundamental informations about subject CMS platforms and vulnerability scanners utilised to research. For research purposes Wordpress and Joomla websites were created and investigated for security by vulnerability scanners OWASP ZAP, Vega, Detectify and Skipfish. Results were grouped by some criteria: vulnerabilities by category and vulnerabilities by threat level. Obtained results were examined in two ways: analysis of residual results, for each website scanning and analysis of aggregated results from all scanners. After that, conclusions about CMS platforms security have been drawn.